KIAT MENYIAPKAN PROPOSAL PENELITIAN TUGAS AKHIR BIDANG BISNIS & MANAJEMEN YANG BAIK & MENARIK - Ignatius Roni Setyawan; Ani Nuraini; Sakti Brata Ismaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
With the passing of Merdeka Belajar Kampus Merdeka (MBKM) (MBKM), all campuses and universities must include the productivity agenda of lecturers and students' scientific work in the level of achievement of the Main Performance Indicators (IKU). One of the triggering factors for the low productivity of lecturers and students' scientific work is the low academic culture at the student level starting from the initial level lectures to the level of the final project course. As an agreement with FMB URINDO partners at the last meeting on October 23, 2021 by zoom, the forms of this PKM activity are 1) Reviewing Webinars & Intensive Coaching Clinic simultaneously. The activity was carried out on Friday 12 November 2021 at 13 – 15 PM by zoom and youtube. Participants in the activity were students who had taken thesis and research methods. The output of the activity is a student final project proposal draft which is more suitable to become a thesis final project or a proposal draft to be accepted in future Kenmendikbudristek competition events. The main ingredient of PKM activities will use the Piching Research Platform from Prof. Robert Faff (The University of Queensland, Australia) which has been widely used in interdisciplinary fields and has proven to be effective. The Pitching Research Platform consists of four main parts, namely; big picture framing; three basic building blocks; two kew questions and unique contribution. Indirectly, these four components of the Pitching Research Platform form the structure of the proposal content for the final thesis, thesis and dissertation. By making the best Pitching Research Platform, the quality of final project proposals for undergraduate, postgraduate and doctoral students will increase because it is easier for each student to make a narrative on the item structure of the proposal content.